Cross-Modal Interaction Between Auditory and Visual Input Impacts Memory Retrieval - Marian, Viorica; Hayakawa, Sayuri; Schroeder, Scott R. (Frontiers in Neuroscience, 2021)
How we perceive and learn about our environment is influenced by our prior experiences and existing representations of the world. Top-down cognitive processes, such as attention and expectations, can alter how we process sensory stimuli, both within a modality (e.g., effects of auditory experience on auditory perception), as well as across modalities (e.g., effects of visual feedback on sound localization). Here, we demonstrate that experience with different types of auditory input (spoken words vs. environmental sounds) modulates how humans encode and later recall concurrently-presented visual objects. Participants viewed a series of line drawings (e.g., picture of a cat) displayed in one of four quadrants while listening to a word or sound that was congruent (e.g., “cat” or meow), incongruent (e.g., “motorcycle” or vroom-vroom), or neutral (e.g., a meaningless pseudoword or a tonal beep) relative to the picture. Following the encoding phase, participants were presented with the original drawings plus new drawings and asked to indicate whether each one was “old” or “new.” If a drawing was designated as “old,” participants then reported where it had been displayed. We find that words and sounds both elicit more accurate memory for what objects were previously seen, but only congruent environmental sounds enhance memory for where objects were positioned – this, despite the fact that the auditory stimuli were not meaningful spatial cues of the objects’ locations on the screen. Given that during real-world listening conditions, environmental sounds, but not words, reliably originate from the location of their referents, listening to sounds may attune the visual dorsal pathway to facilitate attention and memory for objects’ locations. We conclude that audio-visual associations in the environment and in our previous experience jointly contribute to visual memory, strengthening visual encoding through exposure to auditory input.